Quality assurance in genetic testing: a European perspective (Italian Journal of Public Health, 2006)
Genetic testing has moved rapidly from research to clinical use and the issues of quality have not alwaysreceived sufficient attention. In response to these needs to improve the overall quality assurance system forgenetic testing and services there have been several international initiatives that are reviewed here. Themain activities at European level towards improving the quality assurance of genetic testing are described.
Keywords: genetic testing; quality assessment; reference systems; international cooperation